Association Between Opium Consumption and Lipid Profile: A Systematic Review and Meta‐Analysis of Observational Studies - Fatemeh Zahra Gafuori Fard; Yaser Mohammadi; Maryam Rezaei; Seyed Mohammad Riahi (Health Science Reports, 2026)
ABSTRACT Background Opium, traditionally used for its analgesic and sedative properties, has been widely consumed. Given the conflicting evidence regarding its association with lipid profiles, the present study was conducted to investigate the association between opium consumption and lipid profile parameters. Methods A comprehensive search was conducted in PubMed, Scopus, and Web of Science up to May 2025. Search results were screened in two stages by two independent reviewers. Data were extracted and the quality of the included studies was assessed using the JBI checklist. Statistical analysis was performed using STATA‐17. Results A total of 36 studies with 5660 opium users and 11,885 controls were included. The meta‐analysis revealed a significant reduction in total cholesterol (WMD = −4.72, 95% CI: −8.72 to −0.71) and HDL‐C (WMD = −1.95, 95% CI: −3.69 to −0.22), while no significant associations were observed for triglycerides, LDL‐C, Apo‐A1, and Apo‐B100. Notably, gender‐based subgroup analysis showed a significant association with lower TG levels in men and lower TC and LDL‐C levels in women. Meta‐regression analyses showed no statistically significant association between duration of opiate use and lipid parameters. Also, overall study quality was high with no evidence of publication bias. Conclusion This comprehensive meta‐analysis demonstrates that opium consumption is not associated with a clinically favorable lipid profile. While meta‐regression revealed nonsignificant positive trends between the duration of opium use and lipid parameters, the overall dyslipidemic pattern indicates an unfavorable cardiovascular risk profile. Future longitudinal and multinational studies with standardized exposure assessment are essential to clarify the dose–response relationships and long‐term cardiometabolic consequences of opium use.